MENILAI TINGKAT KESEHATAN BANK DENGAN METODE CAMEL DAN PEARLS - Encep Saefullah (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2020)
The financial statements of PT. Bank Tabungan Pensiunan Nasional has decreased over the past 5 years, causing some financial ratios to decrease as well.The purpose of this research is to analyze financial performance with two methods namely CAMEL and PEARLS. What is the ratio of bank soundness if measured by both methods in the period 2013 to 2017.This research was conducted at PT. BTPN using secondary data taken from the Balance Sheet Report, Income and Cost Statements of company growth statistics, the variables used are the bank's financial performance related to CAMEL and PEARLS methods whose results will be classified according to the assessment category of each method. The results of this study note the position of the company's financial performance is assessed by the CAMEL method is in a fairly healthy and healthy position, while the results of the study with the PEARLS method is known in the Protection ratio is in the unhealthy category,this means that there are differences in the two methods of measuring bank soundness.So that it can be seen the difference of these two methods is that it can be seen from the bank growth rate used in the PEARLS method in assessing the bank's soundness. So banks can grow and grow by managing assets owned.